Abdominal obesity and colorectal cancer risk: systematic review and meta-analysis of prospective studies. Issue 6 (12th December 2017) - Dong, Yunlong; Zhou, Jiao; Zhu, Yun; Luo, Linhai; He, Tao; Hu, Hong; Liu, Hao; Zhang, Yingliang; Luo, Dan; Xu, Shuanglan; Xu, Lifen; Liu, Jianping; et al.
Abstract : The association between abdominal obesity (as measured by waist circumference (WC) and waist-to-hip ratio (WHR)) and colorectal cancer (CRC) has not been fully quantified, and the magnitude of CRC risk associated with abdominal obesity is still unclear. A meta-analysis of prospective studies was performed to elucidate the CRC risk associated with abdominal obesity. Pubmed and Embase were searched for studies assessing the association between abdominal obesity and CRC risk. Relative risks (RRs) with 95% confidence intervals (95% CIs) were pooled using random-effects model of meta-analysis. Nineteen prospective cohort studies from eighteen publications were included in this meta-analysis. A total of 12, 837 CRC cases were identified among 1, 343, 560 participants. Greater WC and WHR were significantly associated with increased risk of total colorectal cancer (WC: RR 1.42, 95% CI 1.30, 1.55; WHR: RR 1.39, 95% CI 1.25, 1.53), colon cancer (WC: RR 1.53, 95% CI 1.36, 1.72; WHR: 1.39, 95% CI 1.18, 1.63), and rectal cancer (WC: RR 1.20, 95% CI 1.03, 1.39; WHR: RR 1.22, 95% CI 1.05, 1.42). Subgroup analyses further identified the robustness of the association above. No obvious risk of publication bias was observed. In summary, abdominal obesity may play an important role in the development of CRC.